Evaluation of Prevalence and Features of Coronary Artery Anomalies using Multidetector-row Computed Tomography - Farah Kalsoom, Muhammad Taha Khalil, Mustafa Ali Siddiqi, Sehrish Khalid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the course, origin and termination of coronary artery anomalies in subjects demonstrating various symptoms and undergoing multidetector CT coronary angiography for evaluation of coronary disease. Study Design: Retrospective study Place and duration: Ch.Pervaiz Elahi Institute of Cardiology Multan from January 2021 to January 2022. Methodology: The study included patients who were referred to the radiology department because of suspicion of coronary artery disease. The data of these patients were reviewed for the course and origin of coronary artery anomalies. A 64-slice scanner was used for MDCT coronary angiography. At the start of acquisition contrast arriving coronary arteries were synchronised using the bolus tracking technique. The whole heart was imaged during apnea using 80-90ml iodinated contrast material administered intravenously. Coronary arteries were evaluated using 3-D and multiplanar reformatted images Results: Total of 600 patients who were referred for MDCT coronary angiography. The subjects underwent screening because of various risk factors, chest pain, or similar symptoms. Coronary artery anomalies were diagnosed in 21 out of 600 (3.5%) patients, whose mean age was 52.6±10.8 years and 504 (84%) were male. 3(14%) patients had high take-off of RCA (right coronary right) and 4(19%) of LMCA (left main coronary artery). In 5(24%) patients left circumflex artery (LCx) and left anterior descending artery (LAD) originated separately from the left sinus of Valsalva (LSV). In 3(14%) patients RCA originated from the opposite sinus of Valsalva.RCA anomaly in 1 patient had a malignant course. Conclusion: The study shows that evaluation of coronary artery anomalies can viably be done using CT. Right diagnosis and treatment planning are based upon an understanding of the clinical significance and CT characteristics of different CAAs.